(untitled) (Tanzania Journal for Population studies and Development, 2024)
This article aims to elucidate the impact of religion on humanitarian practices within local communities affected by floods and the resulting contributions to community survival. Empirical data derived from interviews and focus group discussions conducted with community members in Msowero and Mbigiri wards, Kilosa District, in Morogoro Region, forms the basis of the study findings. Both Muslims and Christians perceive assisting the needy as a divine directive and command, with Holy Scriptures such as the Bible and Quran affirming that those helping their fellow humans will receive divine reward. The act of helping the needy is identified as a means of validating one’s faith, expiating sin, demonstrating respect for others, engaging in worship, and fulfilling a duty to God. The study reveals that individuals in flood-affected local communities actively engage in humanitarianism by helping victims. These acts encompass providing basic necessities such as food, clothing, and shelter, facilitating education services by covering school fees and acquiring uniforms for students, and offering health-related services. Such humanitarian practices significantly contribute to community survival by ensuring the availability of essential resources for victims, promoting good health and well-being, and facilitating access to social services, particularly education for children. This article not only highlights how religiously influenced humanitarianism is pivotal for community survival but also underscores the essential role played by individual local community members as crucial contributors to government and development partners’ endeavours in safeguarding people’s well-being during and after natural disasters like floods.